Al-Shāfiʿī against the Kufan school - Melchert, C (Brill, 2021)
One of the short works of al-Shāfiʿī (d. 204/820) is Ikhtilāf ʿAlī wa-ʿAbd Allāh ibn Masʿūd (“the disagreements of ʿAlī and ʿAbd Allāh ibn Masʿūd”). It comprises first quotations of the Companions ʿAlī and Ibn Masʿūd advocating rules that the Kufans reject, secondly counter-reports supporting the rules that al-Shāfiʿī advocates. It seems to be one of the earliest of al-Shāfiʿī’s works. It argues mainly by authority against an undifferentiated Kufan school. It testifies to a time when regional schools were predominant and legal reasoning primitive, also when divisions within Kufa, especially between adherents of raʾy and hadith, were less important than they seemed later. Its argument tends to imply that al-Shāfiʿī’s doctrine is better than the Kufans’ because it is eclectically based on the learning of all centers, suggesting that loyalty to a regional tradition was becoming an embarrassment.